Spinorphin Molecules as Opportunities for Incorporation into Spinorphin@AuNPs Conjugate Systems for Potential Sustained Targeted Delivery to the Brain - Stela Georgieva; Petar Todorov; Jana Tchekalarova (Pharmaceuticals)
Background: This study explores the potential for the synthesis of peptide nanosystems comprising spinorphin molecules (with rhodamine moiety: Rh-S, Rh-S5, and Rh-S6) conjugated with nanoparticles (AuNPs), specifically peptide Rh-S@AuNPs, peptide Rh-S5@AuNPs, and peptide Rh-S6@AuNPs, alongside a comparative analysis of the biological activities of free and conjugated peptides. The examination of the microstructural characteristics of the obtained peptide systems and their physicochemical properties constitutes a key focus of this study. Methods: Zeta (ζ) potential, Fourier transformation infrared (FTIR) spectroscopy, circular dichroism (CD), scanning electron microscopy (SEM-EDS), transmission electron microscopy (TEM), and UV–Vis spectrophotometry were employed to elucidate the structure–activity correlations of the peptide@nano AuNP systems. Results: The zeta potential values for all the Rh-S@AuNPs demonstrate that the samples are electrically stable and resistant to flocculation and coagulation. The absorption of energy quanta from UV–Vis radiation by the novel nanopeptide systems does not substantially influence the distinctive signal of AuNPs, which is situated at around 531 nm. The FTIR measurements indicate the signals associated with the unique functional groups of the peptides, whereas circular dichroism verifies the synthesis of the conjugated nanocomposites of the spinorphin@AuNP type. An analysis of the SEM and TEM data revealed that most AuNPs have a spherical morphology, with an average diameter of around 21.92 ± 6.89 nm. The results of the in vivo studies showed promising findings regarding the anticonvulsant properties of the nanocompounds, especially the Rh-S@AuNP formulation. Conclusions: All the nanocompounds tested demonstrated the ability to reduce generalized tonic–clonic seizures. This suggests that these formulations may effectively target the underlying neuronal hyperexcitability. In addition, the prepared Rh-S@AuNP formulations also showed anticonvulsant activity in the maximal electroshock test performed in mice, which was evident after systemic (intraperitoneal) administration. The study’s findings indicate that conjugates can be synthesized via a straightforward process, rendering them potential therapeutic agents with biological activity.